An Open Platform for High‐Resolution Light‐Based Control of Microscopic Collectives. (1st May 2022) - Rubio Denniss, Ana; Gorochowski, Thomas E.; Hauert, Sabine
Abstract : Engineering microscopic collectives of cells or microrobots is challenging due to the often limited capabilities of the individual agents, the inability to reliably program their motion and local interactions, and difficulties visualizing their behaviors. Herein, a low‐cost, modular, and open‐source Dynamic Optical MicroEnvironment (DOME) is presented with the ability to augment microagent capabilities, and drive collective behaviors using light. The DOME offers an accessible means to study complex multicellular phenomena and implement de‐novo microswarms with desired functionalities. An interactive preprint version of the article can be found at: https://www.authorea.com/doi/full/10.22541/au.164191998.84940186. Abstract : The Dynamic Optical MicroEnvironment (DOME) enables closed‐loop spatiotemporal control of microscopic collectives (e.g., microrobots, microparticles, algae, bacteria, or mammalian cells) using light. The DOME is a low‐cost, open‐source, and fully integrated device that is easy to build using off‐the‐shelf components. Herein, Volvox algae displaying desired augmented capabilities, such as communication, stigmergy, and motion control, essential for future cooperative behaviours, is shown.